A comparative Study of Novel Extramedullary Fixation and Dynamic Hip Screw in the Fixation of Intertrochanteric Fracture: A Finite-Element Analysis - Ding, Kai; Zhu, Yanbin; Wang, Haicheng; Li, Yonglong; Yang, Weijie; Cheng, Xiaodong; Zhang, Yingze; Chen, Wei; Zhang, Qi (Frontiers in Surgery, 2022)
Background Dynamic hip screw (DHS) is one of the most widely internal fixations for stabilizing intertrochanteric fracture, however, with a high risk of postoperative complications. The triangle support fixation plate (TSFP) is developed to reduce the postoperative complications. The purpose of study is to evaluate the biomechanical performance of the DHS and TSFP and demonstrate the rationality of triangular internal fixation for stabilizing intertrochanteric fractures. Methods The CT data of the proximal femur were used to establish finite-element models. Evans type I and IV intertrochanteric fracture were constructed and stabilized with the DHS and TSFP. The Von-Mises stress, maximum principal stress, minimum principal stress, and displacement were used to evaluate the biomechanical effect of two implants on intertrochanteric fracture. Results Under a 600N axial load, the maximum stress and displacement of an intact proximal femur were 13.78 MPa and 1.33 mm, respectively. The peak stresses of the bone in the TSFP were 35.41 MPa and 68.97 MPa for treating Evans type I and IV intertrochanteric fractures, respectively, which were lower than those in the DHS. The maximum overall displacement and relative distance of the fracture surface in the DHS fixation model were 1.66 mm and 0.10 mm for treating Evans type I intertrochanteric fracture, which was 29.59% and 150% higher than that in the TSFP, and were 2.24 mm and 0.75 mm for treating Evans type IV intertrochanteric fracture, which was 42.58% and 650% higher than that in the TSFP. Conclusions In conclusion, the TSFP has obvious advantages in stress distribution and stability than the DHS, providing a promising option for the treatment of intertrochanteric fractures.